Moral fictionalism - Kalderon, Mark Eli, 1964- (Lines of thought., 2005)
This book argues that morality is a fiction by means of which emotional attitudes are conveyed. Kalderon's fictionalism shows that non-cognitivism can manage without controversial semantics.